Identification of Acanthocephala Worm in the Small Intestine of Laying Hens from Yogyakarta and Central Java Province, Indonesia - Prastowo, J.; Sahara, A.; Widayati, I.; Ariyadi , B. (International Journal of Poultry Science, 2015)
This study was conducted to identify the type of Acanthocephala that invaded in the small intestine of laying hens based on morphological examination with Semichon’s Carmine staining. A total of 157 laying hens aged over 50 weeks were used. Worms were collected from the intestine, stored in distilled water at 4°C for 2 days and then stained by Semichon’s Carmine for worm identification. Nineteen laying hens (12%) were infected by worms and 187 Acanthocephala were collected from posterior part of the small intestine. Morphological observation and measurement of worms were the proboscis, trunk, genital system and eggs. The identified Acanthocephala were creamy white without pseudo segmentation, proboscis shaped like a pear with hooks, spines and divided into anterior and posterior parts. The number of hooks on the anterior proboscis were 18-22 rows, each contains 5 hooks, long cylindrical trunk and tapered at both ends. The trunk had no spine with two long Lemniscus and it was not tied. The reproductive system of male worms comprised of testis, cement glands, vesicles gland and bursa of copulatory. The reproductive system of female worms comprised of the uterus and vagina. Eggs were oval shape with 3 layers of walls and contain embryos. Based on morphological examination of Acanthocephala worms, it was concluded that the species was Mediorhynchus gallinarum.